Assessment of the feed additive consisting of Lentilactobacillus buchneri (formerly Lactobacillus buchneri) DSM 12856 for all animal species for the renewal of its authorisation (Lactosan GmbH & Co KG). (24th February 2022) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of Lentilactobacillus buchneri (formerly Lactobacillus buchneri ) DSM 12856 as a technological additive for use in forage for all animal species. The additive aims at improving the production of silage and is authorised for all animal species. The applicant has provided evidence that the additive currently on the market complies with the existing conditions of authorisation. There is no evidence to lead the FEEDAP Panel to reconsider its previous conclusions. Thus, the Panel concludes that the additive remains safe for all animal species, consumers and the environment under the authorised conditions of use. Regarding user safety L. buchneri DSM 12856 is not irritant to skin and eyes but is considered a skin and respiratory sensitiser. There was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.